INTERFAITH MARRIAGE IN THE PERSPECTIVE OF ISLAMIC LAW AND LEGISLATION: INTERFAITH MARRIAGE IN THE PERSPECTIVE OF ISLAMIC LAW AND LEGISLATION - bukhari, bukhari (AL-UKHWAH - JURNAL PENGEMBANGAN MASYARAKAT ISLAM, 2022)
Ulama salaf does not allow Muslim men to marry non-Muslim women absolutely, and others allow marrying kitabiyah (people of the Book), namely Yahudi and Christian women In objective reality, marriage of different religions in Indonesia today has more negative effects than positive effects, such as the problem of family harmony and the future of child religiousness. Sometimes some speculate that the problem can be solved by cultivating tolerance and developing a "climate of freedom" in the family. But, again, it is only an ideal desire then in the legislation it is clear that the constitutional court itself has decided to reject marriages of different religions.